Evaluation of the foot health with baropodometric analysis of acromegaly patients followed after pituitary surgery - Karatoprak, Ayfer Peker; Aydin, Levent; yüksel, Burcu; Demirhan, Yeliz; Baydemir, Canan; Selek, Alev; Cantürk, Zeynep; çetinarslan, Berrin (Bangladesh Journal of Medical Science, 2024)
Background: The exposure to growth hormone (GH) and increase in insulin-like growth factor 1 (IGF-1) in acromegaly can cause various clinical findings related to the cardiovascular, respiratory, and musculoskeletal systems. GH exerts its anabolic effects directly or indirectly through IGF-1, by increasing cell proliferation and maturation in various tissues, including bone, cartilage, skeletal muscle, and tendons. The aim of this study is to analyze these changes using baropodometric gait analysis. Methods: Our study was conducted with a sample of 41 acromegaly patients and 42 control group individuals. Static, dynamic, and stabilometric baropodometric analyses were performed, as well as podoscanner analysis. Results: According to the dynamic and static baropodometric analyses of both groups, the standing load distribution and stabilometric Romberg index findings were similar. However, the acromegaly group showed a higher prevalence of pes planus findings compared to the control group (p<0.003). Conversely, the control group showed a higher incidence of callus and corn formation (p=0.01). Conclusions: Pes planus can disturb the load distribution in the foot, leading to the formation of pressure points. High pressure on the plantar surface of the foot is associated with the development of callus and corn. In this study, although pes planus was more common in the acromegaly group than in the control group, callus and corn formation in the forefoot region were higher in the control group (p=0.01). It was suggested that the soft tissue hypertrophy in acromegaly may be protective against callus and corn formation, which are expected to develop due to pressure. The podiatric approach can be used in other endocrinological diseases that affect the musculoskeletal system, such as acromegaly, especially in diabetic patients. Conducting baropodometric analysis and balancing load distribution with insoles can contribute to reducing the risk of fracture in acromegaly patients. Future studies with larger patient groups, including clinical and radiological findings, can be performed to further evaluate these results. Bangladesh Journal of Medical Science Vol. 23 No. 03 July’24 Page : 698-705